ESTABLISHMENT OF REFERENCE RANGES FOR SERUM THYROID FUNCTION TESTS FOR THE BECKMAN COULTER DXL-800 ANALYZER IN HOSPITAL PUTRAJAYA - SS, Binti Anas; E, Hanif; SA, Suhaymin; AB, Nasruddin (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Thyroid status is best assessed biochemically by measurement of plasma thyroid stimulating hormone (TSH) and free thyroxine (FT4) concentrations. Free tri-iodothyronine (FT3) may be measured if T3 thyrotoxicosis is suspected. The laboratory diagnosis of hyperthyroidism depends on the demonstration of a high plasma concentration of FT4 with a suppressed TSH. The laboratory diagnosis of primary hypothyroidism depends on the findings of high plasma TSH concentration and low FT4 concentration. Accurate and reliable reference intervals are very important for proper diagnosis and patient management. Nearly 80% of medical decisions are made based on laboratory reports. Medical laboratories may choose to use reference ranges (RR) provided by the manufacturer of the reagents used to run such tests. However, the RR given by the manufacturer may not represent the biological variation of the local population. It is best to verify or establish the RR for the tests offered as these RR should represent the local population. METHODOLOGY A cross-sectional and prospective study involving healthy adults were done in Hospital Putrajaya in order to establish the RR for thyroid function tests. Eligible volunteers above 18 years old were invited and had their blood taken and analysed for TSH, Free T4, Free T3 and anti-thyroid peroxidase. These samples were analysed using the Beckman Coulter DxI-800. The data collected were analysed using the SPSS version 22. RESULTS The results from data collected from the local population in Hospital Putrajaya showed correlation with the RR provided by the manufacturer. The study also showed a narrower TSH reference value for subjects age 40 and below. CONCLUSION This study showed that the RR of the local population in Hospital Putrajaya were similar to the RR provided by the manufacturer.